Financial Transparency in the Islamic Social Finance Sector in Supporting Sustainable Development Goals (SDGs): A Systematic Literature Review Analysis (2020–2025) - Lailatul Mubarokah; Gilang Ramadhan; Bahrul Ulum (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
The Islamic social finance sector (Zakat, Infaq, Alms, and Waqf) holds profound theoretical and practical significance as an alternative financing instrument to accelerate the Sustainable Development Goals (SDGs). However, optimizing its impact is often hindered by issues of institutional accountability and low public trust. This study aims to map publication trends, identify the construction of financial transparency protocols, and formulate a model linking Islamic social finance governance to the achievement of SDG target indicators. The method employed is a Systematic Literature Review (SLR) adopting the PRISMA 2020 protocol. Through Publish or Perish (PoP) software utilizing Google Scholar and Dimensions databases, an initial population of 600 documents from the 2020–2025 period was retrieved. Following a rigorous set of inclusion and exclusion criteria—including restricting documents strictly to full-text peer-reviewed journal articles and eliminating conventional public sector studies (village funds)—28 core journal articles were selected for in-depth analysis. The results conclude that financial transparency acts as a crucial enabler that mediates the relationship between sharia compliance and the restoration of public trust. The revival of trust correlates positively with the aggregate growth of public fund collection, which in turn optimizes distribution efficiency to fund SDG pillars precisely, particularly SDG 1 (No Poverty), SDG 2 (Zero Hunger), SDG 4 (Quality Education), SDG 6 (Clean Water), SDG 8 (Decent Work), and SDG 10 (Reduced Inequalities).